Impact of Digital Marketing and Electronic Word of Mouth on Cafe Purchasing Decisions - Yunita, Nindya; Tanjung, Jully Angreani (Management Department Universitas Islam Negeri Sumatera Utara, 2024)
The purpose of this research is to investigate how digital marketing and electronic word-of-mouth affect customers' choices to buy at Pojok Kesawan Cafe. The SPSS 27 program and a multiple linear regression-based approach are used to evaluate this study, which has a quantitative, descriptive research design. surveys to collect information. The research sample consisted of 92 respondents, while the study's population consisted of patrons that visited Pojok Kesawan Cafe between September and November 2024. The sample gathering process used purposive sampling. The data analysis procedure included the use of instrument testing, multiple linear regression testing, classical assumption testing, and hypothesis testing. According to the study's findings, Pojok Kesawan Cafe customers' purchasing decisions are positively and significantly impacted by both (1) digital marketing and (2) electronic word-of-mouth.Keywords: Digital Marketing, Electronic Word of Mouth, and Purchasing Decisions